RELATIONSHIP BETWEEN MORPHOLOGICAL CHARACTERISTICS AND MOTOR ABILITIES OF BOYS AND GIRLS AGED FROM 11-14 IN THE PROVINCE OF VOJVODINA - Igor Beretić (Exercise and Quality of Life)
The aim of this study was to examine the relationship between morphologicalcharacteristics and motor abilities of boys and girls aged from 11 to 14 so that the process ofphysical education could be in line with the dynamics of growth and development as well asthe differences between the sexes. The total sample consisted of 730 subjects, divided intofour age groups of 11, 12, 13 and 14. Eight motor tests were conducted and 9 anthropometricmeasures were taken. The boys of all ages achieved better results in tests of coordination, repetitive and explosive power, while girls of all age groups scored better in flexibility tests. The largest differences between the sexes at the ages of 11 and 12 years were the results ofvariables evaluating motor abilities. At the age of 13, a significant difference in skinfoldthickness was found in favor of girls and at the age of 14 in the voluminousness in favor ofboys. In boys aged from 13 and 14, the increase in body volume was negatively correlatedwith the increase in skinfold thickness, indicating that the increase of voluminousness iscaused by the increase of muscle mass. It is therefore concluded that the linear increase of thedifferences in motor performance tests under 14 years of age is caused by increased musclemass in boys, especially in tests where achievement depends on the strength and productionof force.